Índices gonadosomático y hepatosomático en relación con la maduración y muda del camarón Cryphiops caementarius del río Pativilca (Perú) - Medina M., Marco (2019)
The aim of this study was to determine the gonadosomatic (IGS) and hepatosomatic (IHS) indices in relation to the gonadal maturation and moult stages of the Cryphiops caementarius shrimp from the Pativilca River (Peru). A total of 143 male shrimp (4.07-11.70 cm of total length) and 97 females (1.75-8.02 cm of total length) were used. The shrimp were weighed, measured and the molting state was determined. The hepatopancreas and gonads were removed by dissection, weighed and the ovarian stages determined. During the maturation of the ovary, the IGS increased from 0.97 to 5.01% and the IHS decreased from 5.37 to 4.44%. In mature and non-ovulating females in post-moulting A, the highest IGS was 8.28% and the lowest IHS was 1.72%. In females with immature and non-ovulating ovaries, the IGS increased from 1.40 to 3.38% and in immature and ovigerous females from 0.38 to 1.79%, while the opposite happened in mature non-ovigerous females. In males the IGS varied from 1.74 to 0.78% and the IHS from 5.08 to 5.92% during the moulting cycle. In females the IGS increased as the ovary matured and was maximum in post-moulting A and minimum in post-moulting B2; however, the IHS varied inversely with the IGS. In male shrimp, low IGS and high IHS suggest that they do not invest energy for reproduction.